2000
DOI: 10.1006/dbio.2000.9634
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endogenous Retinoids, Enzymes, Binding Proteins, and Receptors during Early Postimplantation Development in Mouse: Important Role of Retinal Dehydrogenase Type 2 in Synthesis of All-trans-Retinoic Acid

Abstract: Specific combinations of nuclear retinoid receptors acting as ligand-inducible transcription factors mediate the essential role of retinoids in embryonic development. Whereas some data exist on the expression of these receptors during early postimplantation development in mouse, little is known about the enzymes controlling the production of active ligands for the retinoid receptors. Furthermore, at early stages of mouse development virtually no data are available on the presence of endogenous retinoids. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 65 publications
3
78
0
2
Order By: Relevance
“…Even though a targeted mutation of the RXR␣ AF-2 ligand-binding domain shows that this protein domain is important for mouse development (14), there is no evidence that AF-2 needs to bind 9-cis-RA to perform its function. Also, although all-trans-RA is easily detectable in many mammalian tissues (15)(16)(17)(18), detection of 9-cis-RA as originally reported (6) has not been confirmed. Nevertheless, in vitro studies pursuing the mechanism of retinoid signaling suggest that transcriptional activation by RXR homodimers depends on 9-cis-RA (13), and that RAR/RXR heterodimers may in some contexts depend solely on binding of all-trans-RA to the RAR partner, so-called RXR subordination (19); but in other contexts RXR subordination is overcome, and binding of 9-cis-RA to RXR is involved in the transcriptional mechanism (20).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Even though a targeted mutation of the RXR␣ AF-2 ligand-binding domain shows that this protein domain is important for mouse development (14), there is no evidence that AF-2 needs to bind 9-cis-RA to perform its function. Also, although all-trans-RA is easily detectable in many mammalian tissues (15)(16)(17)(18), detection of 9-cis-RA as originally reported (6) has not been confirmed. Nevertheless, in vitro studies pursuing the mechanism of retinoid signaling suggest that transcriptional activation by RXR homodimers depends on 9-cis-RA (13), and that RAR/RXR heterodimers may in some contexts depend solely on binding of all-trans-RA to the RAR partner, so-called RXR subordination (19); but in other contexts RXR subordination is overcome, and binding of 9-cis-RA to RXR is involved in the transcriptional mechanism (20).…”
mentioning
confidence: 79%
“…Because RXRs exhibit binding constants for 9-cis-RA ranging from 14 to 18 nM plus EC 50 values for 9-cis-RA transactivation ranging from 7 to 20 nM (7), our finding of a value Ͻ0.7 nM for 9-cis-RA indicates that there is no evidence that 9-cis-RA is present in embryos at a concentration high enough to regulate RXR. Other studies that have detected all-trans-RA in mouse embryos have also mentioned that 9-cis-RA is undetectable (15,17). Whereas it remains possible that a small population of cells in the embryo may contain sufficient 9-cis-RA to activate RXR, no evidence for this has been reported.…”
Section: Is 9-cis-ra Normally Present In Embryos At a Concentration Highmentioning
confidence: 99%
“…Because it is difficult to measure the intracellular concentration of ATRA and/or other retinoids in the podocytes, different strategies will be required to address this question. It is reported that the distribution of RALDH2 provides the most accurate guide to the localization of ATRA (41)(42)(43)(44). Therefore, studying the transcriptional regulation of RALDH2 gene might be informative to further understand the temporal change of intracellular concentration of ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA synthesis and PCR (40 cycles) was performed as described by Ulven et al (1998). The specific primer pairs are listed in a previous report (Ulven et al, 2000).…”
Section: Mrna Isolation and Rt-pcr Analysismentioning
confidence: 99%